Molecular basis of transfusion dependent beta-thalassemia major patients in Sabah - Teh, Lai Kuan; George, Elizabeth; Lai, Mei I.; Tan, Mary Anne Jin Ai; Wong, Lily; Ismail, Patimah (The Japan Society of Human Genetics, 2014)
Beta-thalassemia is one of the most prevalent inherited diseases and a public health problem in Malaysia. Malaysia is geographically divided into West and East Malaysia. In Sabah, a state in East Malaysia, there are over 1000 estimated cases of β-thalassemia major patients. Accurate population frequency data of the molecular basis of β-thalassemia major are needed for planning its control in the high-risk population of Sabah. Characterization of β-globin gene defects was done in 252 transfusion dependent β-thalassemia patients incorporating few PCR techniques. The study demonstrates that β-thalassemia mutations inherited are ethnically dependent. It is important to note that 86.9% of transfusion-dependent β-thalassemia major patients in Sabah were of the indigenous population and homozygous for a single mutation. The Filipino β0-deletion was a unique mutation found in the indigenous population of Sabah. Mutations common in West Malaysia were found in 11 (4.3%) patients. Four rare mutations (Hb Monroe, CD 8/9, CD 123/124/125 and IVS I-2) were also found. This study is informative on the population genetics of β-thalassemia major in Sabah